2003
DOI: 10.1046/j.1440-1754.2003.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Periextubation caffeine in preterm neonates: A randomized dose response trial

Abstract: This trial indicated there were short-term benefits of decreased apnoea in the immediate periextubation period for ventilated infants born <32 weeks gestation receiving higher doses of caffeine. Further studies with larger numbers of infants assessing longer-term outcomes are necessary to determine the optimal dosing regimen of caffeine in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 20 publications
2
60
2
1
Order By: Relevance
“…In the current work, infants in high-dose group had gained more respiratory benefit as evidenced by less documented apneic episodes and less extubation failure rates, compared with those in low-dose group. In agreement of our results, previous studies which compared different dose regimens of caffeine revealed that the use of higher doses of caffeine was associated with significant reduction of apnea episodes [33] and extubation failure rates [33,34]. Steer et al examined a high-dose regimen of 20 mg/kg versus a low-dose regimen of 5 mg/kg given 24 h before a planned extubation in preterm, less than 30 weeks gestation, infants and found shortterm benefit for the high-dose regimen in reducing the rate of extubation failure with no detected effect on infants' mortality, major neonatal morbidity, death, or severe disability at 12 months corrected age [33].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current work, infants in high-dose group had gained more respiratory benefit as evidenced by less documented apneic episodes and less extubation failure rates, compared with those in low-dose group. In agreement of our results, previous studies which compared different dose regimens of caffeine revealed that the use of higher doses of caffeine was associated with significant reduction of apnea episodes [33] and extubation failure rates [33,34]. Steer et al examined a high-dose regimen of 20 mg/kg versus a low-dose regimen of 5 mg/kg given 24 h before a planned extubation in preterm, less than 30 weeks gestation, infants and found shortterm benefit for the high-dose regimen in reducing the rate of extubation failure with no detected effect on infants' mortality, major neonatal morbidity, death, or severe disability at 12 months corrected age [33].…”
Section: Discussionsupporting
confidence: 93%
“…Two studies revealed that daily administration of 20 mg/kg caffeine citrate starting in the periextubation period was as well tolerated as the use of 5 mg/kg per day [8,33]. Furthermore, a daily maintenance dose of 30 mg/kg caffeine citrate was reported to be administered safely in preterm infants [34].…”
Section: Introductionmentioning
confidence: 99%
“…The practice of early extubation has increased during the last few years and it has been shown that early caffeine reduces reintubation. 21 Infants who received early caffeine may have seemed ready to extubate earlier and had earlier extubation and subsequent decreased duration of mechanical ventilation. This may explain our finding of decreased BPD in the early-caffeine group.…”
Section: Discussionmentioning
confidence: 99%
“…The standard clinical dose of caffeine is not always sufficient to abolish AOP (6,7), potentially leading to the use of higher doses. However, little is known regarding the effects of higher doses of caffeine on the immature brain, in particular its effects on the development of white matter (WM), a brain component that is very vulnerable to injury in preterm infants (7,8).…”
mentioning
confidence: 99%
“…However, little is known regarding the effects of higher doses of caffeine on the immature brain, in particular its effects on the development of white matter (WM), a brain component that is very vulnerable to injury in preterm infants (7,8). Although several studies have assessed the effects of high-dose caffeine on the developing brain, these studies show both beneficial (9,10) and detrimental (11,12) effects.…”
mentioning
confidence: 99%